Targeting STAT3 induces apoptosis and suppresses cell growth and invasion by inactivation of Slug signaling in retinoblastoma - Liang, Haijing (Int J Clin Exp Pathol, 2018)
Objective: Abnormalities in the STAT3 pathway are involved in the oncogenesis of several cancers. However, the mechanism by which dysregulated STAT3 signaling inhibited the progression of human retinoblastoma (RB) has not been elucidated. To investigate the role of targeting STAT3 in RB progression, we inhibited STAT3 with Y79 cells and depleted STAT3 with a siRNA. Results: Our results demonstrate that targeting STAT3 inhibited survival and induced apoptosis of Y79 cells through downregulation of Slug and upregulation of PUMA. In addition, targeting STAT3 inhibited invasion and migration of Y79 cells through downregulation of Slug and upregulation of E-cadherin. Furthermore, Slug overexpression inhibited PUMA and E-cadherin upregulation in the Y79 cells with targeting STAT3. Targeting PUMA and E-cadherin reversed the role of targeting STAT3 in the Y79 cells. Conclusions: our findings showed that targeting STAT3 inhibited survival, invasion, and migration in Y79 cells through inactivation of Slug, resulting in the upregulation of PUMA and E-cadherin, and provide novel evidence that the STAT3/Slug pathway may be a new potential target for therapy of RB.